(untitled) (Orfeu, 2020)
This article reports the free community education movement promoted by the Federal University of Alagoas in the project called JPMB - Pedagogical conferences for fanfare musicians, through the Research Group CEMUPE - Penedo Musicology Center in the State of Alagoas. This extension program also covers some municipalities in the interior of the state, and it characterizes itself today as a process of collective and social learning through musical teaching. It approaches how the academy can mobilize to debate music and public policies on music education in the interior of Alagoas, in the northeast and partnerships with municipal, state and federal governments together with the private sector and educational institutions with others countries.